A continuous pilot-scale system using coal-mine drainage sludge to treat acid mine drainage contaminated with high concentrations of Pb, Zn, and other heavy metals - Cui, M.; Jang, M.; Cho, S.H.; Khim, J.; Cannon, F.S. (2012)
A series of pilot-scale tests were conducted with a continuous system composed of a stirring tank reactor, settling tank, and sand filter. In order to treat acidic drainage from a Pb-Zn mine containing high levels of heavy metals, the potential use of coal-mine drainage sludge (CMDS) was examined. The pilot-scale tests showed that CMDS could effectively neutralize the acidic drainage due to its high alkalinity production. A previous study revealed that calcite and goethite contained in CMDS contributed to dissolutive coprecipitation and complexation with heavy metals. The continuous system not only has high removal efficiencies (97.2-99.8), but also large total rate constants (K total, 0.21-10.18h -1) for all heavy metals. More specifically, the pilot system has a much higher Zn(II) loading rate (45.3gm -3day -1) than other reference systems, such as aerobic wetland coupled with algal mats and anoxic limestone drains. The optimum conditions were found to be a CMDS loading of 280gL -1 and a flow rate of 8Lday -1, and the necessary quantity of CMDS was 91.3gL -1day -1, as the replacement cycle of CMDS was determined to be 70 days. Â© 2012 Elsevier B.V..